Penatalaksanaan Fisioterapi Pada Osteoarthritis Genu Billateral Di Rumah Sakit PKU Muhammadiyah Yogyakarta - Sujarsamsi, Sari Winda Fransisca, Wahyuni, S. Fis, M. Kes (2015)
Background : Osteoarthritis or degenerative disease is also called a disorder of cartilage that is characterized by changes in clinical, histological and radiological. This disease is asymmetrical, no systemic component. Treatment of physiotherapy in condition osteoarthritis genu billateral is to maintenance and rehabilitation motion of the body throughout life make use of handling manually or with equipment. Purpose : To find out treatment of physiotherapy in reducing pain, increase range of motion, increase muscle strength and improving functional ability in condition osteoarthritis genu billateral by using Transcutaneus Electrical Nerve Stimulation (TENS) and exercise therapy (ET). Result : After treatment for six times therapeutic obtained the following result in knee dextra, for silent pain T1 : 4 while of T6 : 2 for tenderness T1 : 5 while of T6 : 3, for the pain motion T1 : 6 while for T6 : 4, in knee sinistra, for silent pain T1 : 3 while of T6 : 1 for tenderness T1 : 4 while of T6 : 2, for the pain motion T1 : 5 while for T6 : 3, for increase range of motion in knee dextra, active motion for T1 : S : 00 - 00 - 950 while for T6 : S : 00 - 00 - 1150, for increase range of motion in knee sinistra, active motion for T1 : S : 00 - 00 - 950 while for T6 : S : 00 - 00 - 1250 , for increase muscle strength of the flexor muscles knee dextra for T1 : 3 while for T6 : 3+, for increase muscle strength of the ekstensor muscles knee dextra for T1 : 3 while for T6 : 3+, for increase muscle strength of the flexor muscles knee sinistra for T1 : 3+ while for T6 : 4, for increase muscle strength of the ekstensor muscles knee sinistra for T1 : 3+ while for T6 : 4, improving functional ability in condition for standing from a seated position for T1 : 4 while for T6 : 3, for walk 15 meters for T1 : 3 while for T6 : 2, for go up the stairs 3 trap for T1 : 4 while for T6 : 3. Conclusion : Transcutaneus Electrical Nerve Stimulation (TENS) and Exercise therapy (ET) can reducing pain, can increase range of motion, increase muscle strength and improve in condition post ORIF fractures of the femur 1/3 left distal.